Perancangan Buku Pop-Up Permainan Tradisional Anak sebagai Media Pelestarian Keaifan Lokal Lombok NTB - Tsania Putri Mahisa; Insanul Qisti Barriyah; Septi Asri Finanda; Moh. Rusnoto Susanto (LPPM Institut Nasional Laa Roiba Bogor, 2022)
This writing aims to (1) describe children's games as ideas or inspiration for the creation of a work of Pop Up Books (2) describe the depiction of the form and process of making Visual Communication Design in the form of a three-dimensional Pop-up Book that elevates Lombok NTB's Traditional Children's Games in order to remain maintain and preserve the local wisdom of the archipelago through children's games. The methods used in the creation of this artwork include exploration and experimentation. In this case, the exploration was carried out by searching for libraries, pictures and all information related to the theme that I took, namely traditional games for children from Lombok, NTB. Then in terms of this exploration, do a sketch activity, which is then visualized in several uses of several bitmap-based applications such as Ibis applications on mobile phones and Coreldraw applications using laptops. The work is done by starting from making a sketch, then designing, printing, then cutting and pasting until finally it becomes a Pop-up book. The results of the discussion and creation are as follows: 1. The theme of the work presented in: Final Project is Traditional Children's Games in Lombok NTB, with the title